Discerning Motivational Interviewing through a spiritual lens—discovering a Christian MI archetype and native MI language. (8th February 2021) - Butler, Mark H.; Gossner, Jacob D.; Barham, Connor C.; Hansen‐Bethea, Madeline C.; Crawford, Misha D.
Abstract: An overarching conceptual perspective on motivational interviewing (MI) captures how it evokes intrinsic motivation for change by relying on four key elements: establishing vision, exploring discrepancy, and building efficacy, which coalesce to resolve for change. We suggest that the Christian narrative and doctrines of creation, fall, and redemption, motivating repentance resolve, invoke these same motivating processes. In this paper we explore these parallels between MI and Christian doctrine and use empirical literature to suggest how secular and religious counselors can enhance their efforts to evoke intrinsic motivation for change with religious clients by employing their "native language" within this framework of MI process.